1999
DOI: 10.1007/bf00833502
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characteristics of surfaces of hardwood and softwood deteriorated by weathering

Abstract: The factors that cause weather-induced deterioration of wood surfaces were determined by chemical and spectroscopic analyses. Albizzia (Paraserianthes falcata Becker.) and sugi (Cryptomeria japonica D. Don) were exposed to two temperate conditions of natural weathering with and without rainfall and to accelerated conditions of artificial weathering coupled with ultraviolet (UV) light irradiation and water flashing. Infrared spectroscopic analysis showed that the oxidative reaction of lignin was observed under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
9

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 9 publications
2
20
0
9
Order By: Relevance
“…Only the colour changes of samples treated with an oil-based coating (C) were significantly lower compared to untreated oak after 3 weeks of artificial weathering ( Figure 2). As mentioned above, high colour changes indicate a degradation of the protective coating layer and leaching of extractives [29] and lignins decomposed using UV light [16]. This result therefore showed that this type of coating provides sufficient protection for oak wood in the initial phase of the weathering test, wherein it prevents the wood from leaching degraded extractives and lignin-see also the initial decrease of L* values (darkening) associated with the increase of a* values (reddening) and b* values (yellowing) after 1 week of weathering ( Figure 2, Table 4).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Only the colour changes of samples treated with an oil-based coating (C) were significantly lower compared to untreated oak after 3 weeks of artificial weathering ( Figure 2). As mentioned above, high colour changes indicate a degradation of the protective coating layer and leaching of extractives [29] and lignins decomposed using UV light [16]. This result therefore showed that this type of coating provides sufficient protection for oak wood in the initial phase of the weathering test, wherein it prevents the wood from leaching degraded extractives and lignin-see also the initial decrease of L* values (darkening) associated with the increase of a* values (reddening) and b* values (yellowing) after 1 week of weathering ( Figure 2, Table 4).…”
Section: Resultsmentioning
confidence: 87%
“…However, if the depolymerized lignins and the extractives are washed out using water, the L* value increases (lightening) and values a* and b* decrease [70,71]. Leaching occurs when wood is exposed to weathering in the native state, or if the continuous protective coating layer is damaged [16]. In the case of natural weathering in the exterior, the wood subsequently turns gray (decrease of L*, a*, b*) due to the deposition of dirt and the effects of moulds or wood-staining fungi [20,72].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Destaca-se nessa região a banda de absorção em cerca de 1510 cm -1 , que tem origem nas estruturas dos anéis aromáticos da lignina. 9,[28][29][30] Estes autores e outros mais 5,18,19,21,22,30,31 fazem uso da área ou altura dessa banda para quantificar as modificações químicas ocorridas na superfície das madeiras.…”
Section: Resultsunclassified
“…9,[28][29][30][31] De modo geral, os valores de números de onda das bandas das quatro madeiras brasileiras descritas na Tabela 1 foram bastante próximos entre si e dos valores observados nos espectros FTIR das madeiras de clima temperado. 8,27,28,29,30 Durante a fotodegradação da madeira, algumas estruturas quí-micas são destruídas e outras são formadas, resultando em variações na intensidade das bandas com o aumento do tempo de irradiação UV. assim como para as leguminosas de clima temperado, as duas principais bandas que sofrem mudanças significativas correspondem ao modo ν(C=o) (1736 cm -1 ) e ao modo ν(C=C) (1510 cm -1 ) para as quatro madeiras tropicais estudadas.…”
Section: Figura 1 Espectros Drift Das Madeiras Estudadasunclassified